Ultrasound predictors of compensated liver cirrhosis in hemodialysis patients with hepatitis C - P Dzekova-Vidimliski; S Dzikova; Gj. Selim; S Gelev; L Trajceska; V Pushevski; A Sikole (Saudi Journal of Kidney Diseases and Transplantation, 2013)
Ultrasound examination was performed in 80 hemodialysis (HD) patients with chronic hepatitis C in order to determine the ultrasound predictors of compensated liver cirrhosis. The ultrasound score (US) was calculated from the morphological parameters (liver size, morphology, surface, echogenicity and spleen volume) and the hemodynamic parameters (portal vein diameter and portal vein mean flow velocity). The US ranged from 0 to 200, with a cut-off value of 66, for discrimination between absence and presence of liver cirrhosis. A logistic regression model with stepwise variable selection was used to determine predictors of the progression of liver disease. According to the calculated US, patients were divided into two groups. The first group consisted of 37 (46.3%) patients with US greater than 66, indicating the presence of compensated liver cirrhosis. The second group included 43 (53.7%) patients without liver cirrhosis, with US equal to or less than 66. The value of liver morphology was significantly higher, but the portal vein flow velocity was significantly lower in patients with compensated liver cirrhosis compared with those without cirrhosis. Furthermore, rounded liver surfaces and increased liver echogenicity were significantly more frequent in patients with compensated liver cirrhosis compared with the non-compensated group. Logistic regression model with stepwise discriminant analysis identified liver morphology, liver echogenicity and portal vein mean flow velocity as independent ultrasound predictors of compensated liver cirrhosis in HD patients with chronic hepatitis C. Ultrasound examination could be used for non-invasive diagnosis of compensated liver cirrhosis, with accurate estimation of the disease severity in HD patients with chronic hepatitis C.